2023
DOI: 10.3390/ijms24076612
|View full text |Cite
|
Sign up to set email alerts
|

Development of New Targeted Nanotherapy Combined with Magneto-Fluorescent Nanoparticles against Colorectal Cancer

Abstract: The need for non-invasive therapies capable of conserving drug efficiency and stability while having specific targetability against colorectal cancer (CRC), has made nanoparticles preferable vehicles and principal building blocks for the development of complex and multi-action anti-tumoral approaches. For that purpose, we herein report the production of a combinatory anti-tumoral nanotherapy using the production of a new targeting towards CRC lines. To do so, Magneto-fluorescent NANO3 nanoparticles were used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 86 publications
0
1
0
Order By: Relevance
“…In addition to mAb, they also modified the NPs with a second targeted agent (an acetazolamide derivative), and the resulting nanosystem was used to transport a combination of two broad-spectrum chemodrugs: doxorubicin and ofloxacin. The results obtained by these authors showed that the developed nanocarrier had a great cellular uptake rate and significant toxicity to the HTC116 colon cancer cell line, so it also has a high potential to be used as a novel nanotherapy agent [ 90 ].…”
Section: Antibody-loaded Nanosystems For the Therapy Of Crcmentioning
confidence: 99%
“…In addition to mAb, they also modified the NPs with a second targeted agent (an acetazolamide derivative), and the resulting nanosystem was used to transport a combination of two broad-spectrum chemodrugs: doxorubicin and ofloxacin. The results obtained by these authors showed that the developed nanocarrier had a great cellular uptake rate and significant toxicity to the HTC116 colon cancer cell line, so it also has a high potential to be used as a novel nanotherapy agent [ 90 ].…”
Section: Antibody-loaded Nanosystems For the Therapy Of Crcmentioning
confidence: 99%